Transformative Disaster Education for Reducing the Knowledge Action Gap among Adolescents: Evidence Synthesis Based on Local Seismicity in West Sumatra - Reza, Fakhri; Adi Subiyanto; Sutanto (International journal of technology and education research, 2025)
West Sumatra, Indonesia, faces a critical dual seismic hazard from the Sunda Megathrust and the active Sumatra Fault System, resulting in repetitive destructive earthquakes and high structural vulnerability. This study investigates the effectiveness of disaster preparedness among adolescents (aged 10–24), a strategic demographic group comprising over 25% of the population. Using Evidence Synthesis via a Descriptive-Qualitative Library Research approach, this paper analyzes the convergence of local seismotectonic risks and social preparedness models.The synthesis reveals a significant knowledge–action gap (preparedness paradox): while theoretical disaster knowledge among students is high, their practical readiness and self-efficacy are moderate to low. This discrepancy is primarily driven by the insufficient contextualization of education to specific local seismic threats. We argue that structural mitigation must be urgently complemented by strengthening social adaptive capacity. The study advocates for implementing transformative disaster education that formally integrates local seismic data, hazard maps, and scenario-based psychomotor training. This model is essential for fostering adaptive competence and leveraging adolescents as pivotal agents of long-term community resilience and disaster risk reduction in this high-risk environment.